2014
DOI: 10.1371/journal.pone.0097904
|View full text |Cite
|
Sign up to set email alerts
|

Low Medium pH Value Enhances Anthocyanin Accumulation in Malus Crabapple Leaves

Abstract: Anthocyanin is a critical factor involved in coloration of plant tissues, but the mechanism how medium pH values affect anthocyanin accumulation in woody plants is unknown. We analyzed anthocyanin composition and the expression of elements encoding anthocyanin and flavonols biosynthesis underlying different medium pH values by using three different leave color type cultivars. HPLC analysis demonstrated that high medium pH values treatment induced a dramatic decrease in the concentration of cyaniding in crabapp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 28 publications
5
26
0
Order By: Relevance
“…Previous studies concluded that a suitable pH can promote anthocyanin biosynthesis in specific tissues of some plant species, including carrot and crabapple [12, 15]. In crabapple seedlings, the synthesis of anthocyanins is beneficial in moderately acidic environments [15]. Consistent with the results of previous studies, we observed that under moderately acidic conditions, especially at pH 6.0, anthocyanins accumulated considerably in apple calli.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Previous studies concluded that a suitable pH can promote anthocyanin biosynthesis in specific tissues of some plant species, including carrot and crabapple [12, 15]. In crabapple seedlings, the synthesis of anthocyanins is beneficial in moderately acidic environments [15]. Consistent with the results of previous studies, we observed that under moderately acidic conditions, especially at pH 6.0, anthocyanins accumulated considerably in apple calli.…”
Section: Discussionsupporting
confidence: 91%
“…Environmental pH is one of the important physical and chemical factors affecting the metabolic activities of plant tissues. Previous studies concluded that a suitable pH can promote anthocyanin biosynthesis in specific tissues of some plant species, including carrot and crabapple [12, 15]. In crabapple seedlings, the synthesis of anthocyanins is beneficial in moderately acidic environments [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 'Prairifire' plantlets, significant inductions of anthocyanin, flavonols and apigenin were noted in response to the photoperiod; however, the expression of MYB10 did not change in response to the photoperiod, suggesting that MYB10 may not be involved in controlling the biosynthesis of these flavonoid compounds under different photoperiod treatments. Zhang et al (2014) found that in the leaves of 'Royalty', 'Prairifire' and 'Flame' plantlets, different MYB transcription factors function as regulators of leaf color after pH induction. In 'Prairifire' plantlets, the question of whether other MYB transcription factor(s) are involved in the regulatory effect of photoperiod on flavonoid biosynthesis requires further study.…”
Section: Possible Regulatory Model For Light-induced Malus Crabapple mentioning
confidence: 99%
“…Anthocyanin concentrations in the petals of all three crabapple cultivars, as well as transgenic tobacco petals, were measured by high-performance liquid chromatography (HPLC) as described by Zhang et al (2014). Each 1 g sample was powdered in a mortar and pestle in liquid nitrogen, then 1.0 ml of extraction buffer [70:27:2:1 (v/v/v/v) mix of methanol: water: formic acid: trifluoroacetic acid] was added and the mixture was stored overnight in the dark at 4°C.…”
Section: Measurement Of Anthocyanin Contentmentioning
confidence: 99%